Agricultural prices during drought in Ethiopia: An assessment using national producer data (January 2014 to January 2016) - Bachewe, Fantu Nisrane; Yimer, Feiruz; Minten, Bart; Dorosh, Paul A. (International Food Policy Research Institute, 2016)
We analyze the evolution of crop and livestock producer prices and wages of unskilled laborers in Ethiopia over the January 2014 to January 2016 period, during which time the country was massively impacted by El Niño triggered droughts, which started in 2015. The analyses reveal no evidence of widespread adverse price effects of the drought in the labor and cereal markets. Real prices of the major cereals were lower at the beginning of 2016 compared to two years earlier, especially for maize, sorghum and wheat, the crops that make up the major source of calories in the areas that were most hit by the drought. Conversely, prices of root crops and pulses increased. However, given the large importance attached to cereal consumption, the overall real food consumption basket price has declined compared to two years earlier. In particular, the decline in the cost of cereals in the food basket was estimated at 11.2 percent at the national level. However, the overall declines were lower in drought-affected (decline of 8 percent) than in non-drought affected areas (decline of 14 percent), indicating the adverse effect of failed harvests in the former areas. Considering crop and livestock prices jointly reveals that livestock-cereal terms of trade declined in the worst affected areas, mainly because livestock prices declined faster than cereal prices in such areas. In contrast, the livestock-cereal terms of trade considerably improved in areas less affected by the drought. The fluctuating behavior of cereal prices since January 2015 strikingly contrasts with the situation during the major drought of 1997/98. During that period, cereal production declined by 25 percent compared to the year before, with significant simultaneous real price increases of between 15 and 45 percent.